Integrated Sulphur Management in Rapeseed (Brassica campestris)-Blackgram (Vigna mungo) Sequence in an Inceptisol of Assam - Basumatary, A. (Journal of the Indian Society of Soil Science, 2019)
A field experiment was conducted in three consecutive years during 2012-15 at Instructional cum Research Farm, Assam Agricultural University, Jorhat, Assam to assess the effect of integrated sulphur (S) management on soil fertility status and crop yields under rapeseed-blackgram sequence. The present study comprised of ten treatments, consisting of three levels of S either alone or in different combinations with farmyard manure (FYM), biofertilizer and lime. The results indicated that application of 30 kg S ha-1 along with 50% recommended dose of NPK plus 1/10 lime plus 2 t FYM ha-1 produced the highest seed yield (10.1 q ha-1 and uptake of N, P, K and S (74.0, 9.98, 59.3 and 12.3 kg ha-1) by rapeseed, respectively and its residual effect was also found prominent in producing maximum grain yield (9.4 q ha-1) and uptake of N, P, K and S (42.7, 5.06, 14.5 and 4.25 kg ha-1) by blackgram, respectively. Organic carbon and available primary and secondary nutrient status were found to be highest in treatment receiving application of 30 kg S ha-1 along with 50% recommended dose of NPK plus 1/10 lime plus 2 t FYM ha-1 and exhibited an improvement of 1.9 g kg-1, 48.5 kg ha-1, 3.6 kg ha-1 and 5.3 mg kg-1 of organic carbon, available N, P and S, respectively over initial value after harvest of three cycle of cropping sequence.